Effect of hyperbaric oxygen treatment in a rat model of abdominal aortic aneurysm - (:unkn) unknown (UNDERSEA & HYPERBARIC MEDICAL SOC INC, 2014)
Matrix metalloproteinase (MMP) plays a pivotal role in the pathophysiology of abdominal aortic aneurysms (AAA). Experimental studies have demonstrated that hyperbaric oxygen (HBO2) therapy decreases MMP levels in different tissues. However, the effect of HBO2 therapy on AAA has yet to be investigated. This study aimed to examine the effects of HBO2 on MMPs in an experimental AAA model. The model was implemented with CaCl2 in 12-week-old male Wistar albino rats. The rats were randomized into four groups: Group I: received NaCl (n=6) (Sham group); Group II: received NaCl and were treated with HBO2 (n=6); Group III: received CaCl2 (n=6); and Group IV: received CaCl2 and were treated with HBO2 (n=6). HBO2 therapy was applied for five of seven days over a period of six weeks. Although in the CaCl2 groups, aortic diameters were significantly higher than the NaCl groups (p<0.05), there was no difference between pre- and post-HBO2 in the CaCl2 groups (p>0.05). In the CaCl2 group, the MMP-2 and MMP-9 levels were significantly higher than those in the NaCl group (p<0.05). HBO2 therapy had no statistically significant effect on the MMP-2 and MMP-9 levels in Groups III and IV. However, it was observed that both levels clearly decreased in Group IV. In conclusion, the study suggested that HBO2 may have favorable effects on MMP levels.
Keywords: MATRIX-METALLOPROTEINASE-9; ATHEROSCLEROSIS; DEGRADATION; ISCHEMIA